2016
DOI: 10.1139/cjfr-2016-0061
|View full text |Cite
|
Sign up to set email alerts
|

Tree light capture and spatial variability of understory light increase with species mixing and tree size heterogeneity

Abstract: Mixed and multi-layered forest ecosystems are sometimes more productive than monospecific and single-layered ones. It has been suggested that trees of different species and sizes occupy complementary positions in space which would act as a mechanism to increase canopy light interception and wood production. However, greater canopy light interception reduces the average amount and variability of transmitted radiation offering fewer opportunities for all species to regenerate and to maintain forest heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 57 publications
1
22
0
1
Order By: Relevance
“…This is most likely due to the complementary shrub layer that was high in plots with a rather open canopy and lower under closed canopies. In conclusion, we do find indication for a higher light interception at the tree canopy level if tree diversity increases (Jucker et al., ; Ligot et al., ), but the complementary shrub layer effectively homogenizes light transmittance to the forest floor across species combinations.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…This is most likely due to the complementary shrub layer that was high in plots with a rather open canopy and lower under closed canopies. In conclusion, we do find indication for a higher light interception at the tree canopy level if tree diversity increases (Jucker et al., ; Ligot et al., ), but the complementary shrub layer effectively homogenizes light transmittance to the forest floor across species combinations.…”
Section: Discussionmentioning
confidence: 57%
“…Two different studies using a computer model of broadleaf and coniferous trees found a complementarity effect. Light interception in mixed stands was intermediate between the interception values in monocultures but higher than expected if the effects would be purely additive (Forrester et al, 2017;Ligot et al, 2016). The three mentioned studies focus on forests in the stem exclusion phase; however, evidence for higher light interception in more diverse forests from field studies in mature forests in the understory re-initiation stage is lacking.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Positive correlations among site-level structural complexity traits, vegetation area index, and species diversity indices support the hypothesis (Gough et al 2016) that canopies require the crown architectural variety supplied by a diverse plant community and, additionally, a critical mass of vegetation with which to build complex structure. Multilayered, heterogeneously arranged canopies absorb more light (Ligot et al 2016) and they contain a complement of sun and shade leaves functioning optimally under a range of light conditions. This finding is congruent with theory and modeling asserting that structurally complex forests composed of species and individuals possessing a diversity of leaf physiological traits are more optimally organized to acquire and use light to assimilate carbon (Anten 2016).…”
Section: Discussionmentioning
confidence: 99%